Using persuasive systems design model to evaluate “Cuida tu Ánimo”: an internet-based pilot program for prevention and early intervention of adolescent depression - Parada Zelada, Fernando; Martínez, Vania; Espinosa, H. Daniel; Bauer, Stephanie; Moessner, Markus (Telemedicine and e-health, 2019)
“Cuida tu Ánimo” (CTA [Take Care of Your Mood]) is an internet-based program for prevention and early intervention of adolescent depression implemented in Chile and Colombia. In the pilot application of the program, participants interacted with the program through a website that provided psychoeducational information, chat, and telephone appointments as well as monitoring and feedback messages.